2021
DOI: 10.1371/journal.pntd.0009758
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites in “Invisible Populations”: A cross-sectional survey in riverine populations in the remote western Brazilian Amazon

Abstract: In the Brazilian Amazon, long distances, low healthcare coverage, common use of ineffective or deleterious self-care practices, and resistance to seeking medical assistance have an impact on access to antivenom treatment. This study aimed to estimate snakebite underreporting, and analyze barriers that prevent victims from obtaining healthcare in communities located in 15 municipalities on the banks of the Solimões, Juruá and Purus Rivers, in the remote Western Brazilian Amazon. Information on the participants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
(83 reference statements)
0
20
1
Order By: Relevance
“…Sixteen days after the snakebite, she returned for a dressing change; assessment of the wound revealed red nodules and perilesional calor (heat) in the posterior area of the left leg. A complete blood cell count demonstrated the following: erythrocytes, 3.9 ×10 6 /mm 3 ; hematocrit, 30.64%; hemoglobin, 10.11 g/dL; and platelets, 578,000/mm 3. These findings indicated reduction in the risk of local bleeding and signs of secondary infection.…”
Section: Casementioning
confidence: 90%
See 1 more Smart Citation
“…Sixteen days after the snakebite, she returned for a dressing change; assessment of the wound revealed red nodules and perilesional calor (heat) in the posterior area of the left leg. A complete blood cell count demonstrated the following: erythrocytes, 3.9 ×10 6 /mm 3 ; hematocrit, 30.64%; hemoglobin, 10.11 g/dL; and platelets, 578,000/mm 3. These findings indicated reduction in the risk of local bleeding and signs of secondary infection.…”
Section: Casementioning
confidence: 90%
“…2 However, we recognize that the official number of cases, and even deaths, is underestimated due to the challenges related to the remote nature of area where these bites often occur and the need to seek care at centers located far from where the bite occurs. 3 The main challenges arise from the need to travel great geographic distances for health care and the prohibitive costs of air travel. Over a period of 6 years (2010-2015), a descriptive study that focused on snakebite envenomation in the Brazilian Amazon reported 9386 cases; 81% were caused by Bothrops species (a genus of venomous pit vipers).…”
Section: Introductionmentioning
confidence: 99%
“…However, contact between different health systems often leads to some kind of conflict or competition [ 40 ]. Regarding SBEs, the use of folk medicine and traditional self-care practices are often recorded around the world as the cause of late medical assistance and poor prognosis [ 41 44 ]. Our results do not support the simplistic thought that the belief in the efficacy of traditional practices delays the decision to seek the health service in indigenous villagers, as indigenous caregivers are not against transporting patients to the hospital; on the contrary, they recommend referral in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Given the great diversity of indigenous ethnicities, the current literature is not comprehensive, but it does provide some information on how indigenous peoples in the Brazilian Amazon care for themselves and seek traditional care for snakebites [ 10 , 17 , 18 ]. Minimal research, however, has been conducted on how indigenous peoples access and utilize the health system for snakebite treatment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%